OUTCOMES OF FLEXIBLE URETEROSCOPIC LASER LITHOTRIPSY FOR UPPER URETERAL STONES AT VIET TIEP FRIENDSHIP HOSPITAL FACILITY NO. 2 (Vietnam Journal of Community Medicine, 2026)
Objectives: to evaluate result of flexible ureteroscopy lithiotripsy in treatment of upper 1/3 ureteral stone using holmium laser in vietiep friendship hospital facility no.02Materials and methods: Retrospective study of 40 upper 1/3 ureteral stone cases, treat by retrograde flexible ureteroscopy lithiotripsy using Holmium laser in Viet Tiep friendship hospital facility no.02 from January, 2024 to June, 2025.Result: Mean age is 53.6 ± 15.1, percentage of male patients is 77.5%, while female patients account for 22.5%. Renal colic accounts for 97.5%, dysuria accounts for 55%, fever accounts for 7.5% of number of patients in reasons for hospital admission. Patients who have renal stone combine with upper ureteral stone account for 37.5%, patients with only ureteral stone account for 62.5%. Mean total burden of stone is 14.5 ± 6.4 mm. Mean operating time is 89.25 ± 39.77 minutes. Early stone clear rate is 72.5%. Mean post operative time is 3.68 ± 1.83 days.Conclusion: Flexible ureteroscopy lithiotripsy in treatment of upper 1/3 ureteral stone using holmium laser is a safe, effective method with low rate of complication, short hospitalization time.
Keywords: upper ureteral stone, flexible ureteroscopy lithiotripsy